Tropical Pacific late Cenozoic Iodine/Calcium from planktic foraminifera species from IODP site 321-U1338 - Katrina Nilsson-Kerr; Babette A A Hoogakker; Dharma Reyes-Macaya; Helge Arne Winkelbauer; Elliott Hamilton; Simon Chenery; Catherine V Davis; Melanie J Leng (PANGAEA, 2025)
We apply the Iodine to Calcium (I/Ca) ratio in planktic foraminifera to reconstruct oceanic oxygen across the late Cenozoic. The data includes I/Ca ratios from planktic foraminifera species inhabiting a range of inferred depths within the water column as well as stable oxygen and carbon isotopes from benthic and planktic foraminifera species. Geochemical data spans the late Cenozoic (16 - 0 Ma) from across the tropical Pacific Ocean.